ANALISIS PENGARUH MOTIVASI DAN SIKAP TERHADAP MINAT BERWIRAUSAHA MAHASISWA FEBI IAIN LHOKSEUMAWE - Putri, Juliana; Zulfa, Zulfa (Faculty of Islamic Economics and Business, IAIN Lhokseumawe, 2020)
Indonesia is a developing country with a high population growth rate, along with the increasing population in Indonesia, the competition for jobs is getting more competitive, while the job opportunities offered are limited, so it demands young people and students to be more creative through entrepreneurship. Entrepreneurship education began to be taught in schools, both high school and university, including at the State Islamic Institute of Lhokseumawe. This teaching is expected to be able to motivate and increase student interest in entrepreneurship. This study aims to determine the effect of motivation and attitudes partially and simultaneously on entrepreneurial interest using quantitative methods. Sampling using purposive sampling technique. Data collection was carried out by distributing online questionnaires as many as 92 students as respondents. Data processing with multiple linear regression testing. The results showed that (1) Motivation was able to influence interest in entrepreneurship in FEBI IAIN Lhokseumawe students, (2) attitudes were able to influence interest in entrepreneurship in FEBI IAIN Lhokseumawe students, (3) motivation and attitude were simultaneously able to influence interest in entrepreneurship in FEBI IAIN Lhokseumawe students. Keywords: Motivation, Attitude, Entrepreneurial Interest. Abstrak Indonesia merupakan negara berkembang dengan tingkat pertumbuhan penduduk yang tinggi, seiring dengan bertambahnya jumlah penduduk di Indonesia persaingan mencari pekerjaan semakin kompetitif sementara lapangan kerja yang ditawarkan terbatas sehingga menuntut kaum muda dan mahasiswa untuk lebih kreatif melalui kewirausahaan. Pendidikan kewirausahaan mulai diajarkan disekolah-sekolah, baik sekolah menengah maupun perguruan tinggi, termasuk di Institut Agama Islam Negeri Lhokseumawe. Pengajaran ini diharapkan mampu memotisivasi dan meningkatkan minat mahasiswa dalam berwirausaha. Penelitian ini bertujuan untuk mengetahui pengaruh motivasi dan sikap secara parsial dan simultan terhadap minat berwirausaha dengan menggunakan metode kuantitatif. Pengambilan sampel menggunakan teknik purposive sampling. Pengumpulan data dilakukan dengan penyebaran kuesioner online sebanyak 92 mahasiswa sebagai responden. Pengolahan data dengan pengujian regresi linier berganda. Hasil penelitian menunjukkan bahwa (1) Motivasi mampu mempengaruhi minat berwirausaha pada mahasiswa FEBI IAIN Lhokseumawe, (2) sikap mampu mempengaruhi minat berwirausaha pada mahasiswa FEBI IAIN Lhokseumawe, (3) motivasi dan sikap secara simultan mampu mempengaruhi minat berwirausaha pada mahasiswa FEBI IAIN Lhokseumawe. Kata kunci: Motivasi, Sikap, Minat Berwirausaha